Bailout and Conglomeration - Kim, Se-Jik (IMF Working Papers; Working Paper ;, 1999)
The paper suggests that when firms differ stochastically in their productivity, a bank may find it optimal not to bail out the failed nonconglomerate firms at all, but to bail out conglomerates fully. Expectation of such bailout policy may encourage risk-averse firms to join a conglomerate to minimize the risk of liquidation. Furthermore, in case of private information, bad firms follow good firms' decision on conglomeration to hide their type. Finally, the paper discusses the impact of conglomeration on the debt-equity ratio and the expansion of existing conglomerates through mergers and acquisitions.